ZAB YTKI ZE STOPÓW MIEDZI Z CMENTARZYSKA SKA NDYNAWSKIEGO W B RZYNIE, POW. PUCKI, W ŚWIETLE ANAL IZ METAL OZNAWCZYCH. UWAG I NAD SPOSOBEM POZYSKIWANIA SUROWCA W OKRESIE WĘDRÓWEK LU DÓW - Strobin , Anna; Strobin, Jarosław (Slavia Antiqua. Rocznik poświęcony starożytnościom słowiańskim, 2020)
Archaeological artefacts made of copper alloys are a particularly valuable source of knowledge about ancient societies; in recent years these finds have been more and more often analysed in terms of their chemical composition. Observations based on the results of these analyses are conducive to indicating alloys characteristic of specific chronological periods and to considering the origin of the materials and the operations of workshops.